Trauma a social theory - Alexander, Jeffrey C. 1947- (Polity, 2012)
In this book Jeffrey C. Alexander develops an original social theory of trauma and uses it to carry out a series of empirical investigations into social suffering around the globe. Alexander argues that traumas are not merely psychological but collective experiences, and that trauma work plays a key role in defining the origins and outcomes of critical social conflicts. He outlines a model of trauma-work that relates interests of carrier groups, competing narrative identifications of victim and perpetrator, utopian and dystopian proposals for trauma resolution, the performative power of constructed events, and the distribution of organizational resources. Alexander explores these processes in richly textured case studies of cultural-trauma origins and effects, from the universalism of the Holocaust to the particularism of the Israeli right, from post-colonial battles over the Partition of India and Pakistan to the invisibility of the Rape of Nanjing in Maoist China. In a particularly controversial chapter, Alexander describes the idealizing discourse of globalization as a trauma-response to the Cold War. -- Back cover.